Takhrij and Syarah Hadith of Chemistry: Halalness and The Benefits of Garlic - Siti Nur Aliyah; Cermi City Mulyanti; Nurhidayati Amaliah; Riska Puspita Sari; Irma Riyani (UIN Sunan Gunung Djati Bandung, 2021)
The purpose of this research is to discuss the hadith of the Prophet about garlic. This research method is qualitative through the approach of takhrij and sharah hadith with chemical analysis. The result and discussion of this study is the health benefits of garlic according to a scientific perspective. The conclusion of this research is takhrij and syarah hadith of the Prophet about the permissibility of eating garlic which is also beneficial for health from a scientific perspective.